A Robust pH Sensing Module Utilizing Reproducible Structural Colour Fabricated by Two-Photon Polymerisation - Bradley, Louise; Qian, Jing; Tskhe, Yekaterina; Florea, Larisa; Delaney, Colm (My University, 2025)
Photonic structures integrated with responsive photoresists have garnered significant attention, particularly following the advancements in two photon lithography. The pH responsive photonic array presented exhibits robust structural stability and generates progressively changing structural colours in transmission across various pH buffered solutions, highlighting their strong potential for biosensing applications.
EOSAM 2025
PUBLISHED